Gender influence on schizophrenia-relevant abnormalities in a cuprizone demyelination model - Valeiras, Brenda (2014)
The aim of this study was to determine whether early demyelination can impact behavior in young adulthood. For this purpose, albino Wistar rats of either sex were exposed to cuprizone (CPZ) in two different intoxication protocols: one group was intoxicated before weaning (CPZ-BW), from postnatal day 7 (P7) to P21, through maternal milk, whereas the other group was intoxicated after weaning (CPZ-AW), from P21 to P35. After treatment, rats were returned to a normal diet until P90 when behavioral studies were performed. Both treatments produced marked demyelination in the corpus callosum and retraction of cortical myelin fibers. The subsequent normal diet allowed for effective remyelination at P90. Interestingly, CPZ-AW correlated with significant behavioral and neurochemical changes in a gender-dependent manner. CPZ-AW treatment altered both the number of social activities and the latency to the first social interaction in males, while also highly compromising recognition-related activities. In addition, only P90 males treated AW showed a hyperdopaminergic striatum, confirmed by an increase in tyrosine hydroxylase expression and in dopamine levels. Our results suggest that the timing of demyelination significantly influences the development of altered behavior, particularly in adult males.